Peran Literasi Keuangan Islam dalam Adopsi Layanan Keuangan Digital: Analisis Bibliometrik dan Tinjauan Literatur - Indri, Indri; Agustina, Ahadiah; Hidayanti, Nur Fitri; Ariani, Zaenafi; Hulaimi, Ahmad; Dewi, Novi Yanti Sandra (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to examine the role of Islamic financial literacy in encouraging the adoption of digital financial services through a library research approach with an integrative review method. This review synthesizes findings from various scholarly articles published between 2015 and 2024 and obtained from trusted databases such as Google Scholar, Scopus, DOAJ, and Scispace. Strict inclusion and exclusion criteria were applied to ensure the relevance and quality of the sources. The analysis shows that Islamic financial literacy plays an important role in shaping trust and encouraging the use of sharia-based digital financial services. The understanding of sharia principles such as the prohibition of usury, fairness and transparency is a crucial factor in the adoption process. However, the study also found literacy gaps and limited access to education in some regions. This study highlights the importance of strengthening Islamic financial literacy as a foundation for the development of an inclusive and sustainable Islamic digital finance ecosystem. The findings provide practical implications for regulators, service providers and stakeholders in designing educational strategies and policies based on Islamic values.Abstrak: Penelitian ini bertujuan untuk mengkaji peran literasi keuangan Islam dalam mendorong adopsi layanan keuangan digital melalui pendekatan library research dengan metode integrative review. Kajian ini menyintesis temuan dari berbagai artikel ilmiah yang dipublikasikan antara tahun 2015 hingga 2024 dan diperoleh dari basis data terpercaya seperti Google Scholar, Scopus, DOAJ, dan Scispace. Kriteria inklusi dan eksklusi diterapkan secara ketat untuk memastikan relevansi dan kualitas sumber. Hasil analisis menunjukkan bahwa literasi keuangan Islam berperan penting dalam membentuk kepercayaan serta mendorong penggunaan layanan keuangan digital berbasis syariah. Pemahaman terhadap prinsip syariah seperti larangan riba, keadilan, dan transparansi menjadi faktor krusial dalam proses adopsi tersebut. Namun, kajian juga menemukan adanya kesenjangan literasi dan keterbatasan akses edukasi di sejumlah wilayah. Studi ini menyoroti pentingnya penguatan literasi keuangan Islam sebagai fondasi bagi pengembangan ekosistem keuangan digital syariah yang inklusif dan berkelanjutan. Temuan ini memberikan implikasi praktis bagi regulator, penyedia layanan, dan pemangku kepentingan dalam merancang strategi edukatif dan kebijakan berbasis nilai-nilai syariah.